APPLICATION OF PRINCIPLES OF PUBLIC SERVICE ETHICS IN GEMPOL DISTRICT OFFICE - Moch Wahid (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This research plan is to decide on the use of ethical principles in open administration at the Gempol District Office. The motivation behind this research is that in general the improvement of the framework and techniques of public service administration provided by the regional apparatus must be carried out with careful consideration so that it is believed to create a good perspective from the region and the apparatus that offers the type of assistance. The Pasuruan Regency Government supports Bureaucratic Reform, namely towards a Clean, Accountable and Serving bureaucracy which is a value that is reflected in the implementation of public service administration by devices at the Gempol District Office with proper behavior so that work can be done easily until it is finished.